The Targeted Approach in Implementing the Industrial Policy of Ukraine in the Conditions of the Increasing Import Dependence - Salikhova, O. B.; Krekhivskyi, O. V. (Statistics of Ukraine, 2021)
The global practice of the target approach in implementing the innovation policy in industry is analyzed. It is shown that this approach has long been relied upon by the Chinese government in carrying out the certification of high tech enterprises. The criteria by which high tech enterprises in China are identified are revealed. It is found that the companies with the granted certificate have a number of preferences from the government, e. g.: preferential regime for tax on profit; exemption from or reduction of tax on profit of the qualified income from technology transfer; accelerated depreciation of fixed assets; priority in the issuance of permit on office or industrial lands; subsidies for rental payments; prolongation of the period for carrying forward business losses; priority in the assistance from government support funds at all the levels. It is shown that the Chinese government used the targeted approach to stop the spread of COVID-19 epidemic and halt the rapid industry decline, by charging the National Commission on Development and Reforms and the Ministry of Industry and Information Technologies with the responsibility for making the nomenclature of business entities engaged in the manufacturing of medical protective clothing, insulating clothing, medical and protective civil masks, COVID testing, sterilizers; procurement and storage of medical materials; information and communication equipment and service systems for reaction on the epidemic, as well as the companies taking on the assignments on transportation and sales of the materials. Pursuant to this Directive, nomenclatures of key companies were created in China, for implementing measures on prevention and control of epidemics (the national nomenclature and local nomenclatures). This approach allowed public authorities to exchange information about the condition of these companies and financial preferences and preferential loans provided to them. It is shown that the need for implementing the targeted approach in building up high tech industries was substantiated in Ukraine as early as in 2010, but in spite of the arguments and successful analogous practice in China the proposed targeted approach is yet to be launched. The following measures would be expedient in Ukraine in the conditions of crisis caused by COVID-19 epidemic and in view of the growing dependence on imports of certain categories of goods, hence, the increasing threats to the industry development: elaborate a methodology for identification of advanced technology products and create, on its basis, the Ukrainian State Register of High Tech Industrial Goods; identify high tech goods for industrial purposes (intermediate and capital ones), which ensure continuous operation of Ukrainian companies, with making up their Nomenclature; elaborate methodological tools for qualifying business entities – residents of Ukraine as high tech ones, and create, on its basis, the Ukrainian State Register of High Tech Industrial Companies.